2007
DOI: 10.1021/ac070500b
|View full text |Cite
|
Sign up to set email alerts
|

Density-Based Diamagnetic Separation:  Devices for Detecting Binding Events and for Collecting Unlabeled Diamagnetic Particles in Paramagnetic Solutions

Abstract: This paper describes the fabrication of a fluidic device for detecting and separating diamagnetic materials that differ in density. The basis for the separation is the balance of the magnetic and gravitational forces on diamagnetic materials suspended in a paramagnetic medium. The paper demonstrates two applications of separations involving particles suspended in static fluids for detecting the following: (i) the binding of streptavidin to solid-supported biotin and (ii) the binding of citrate-capped gold nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
122
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 43 publications
0
122
0
10
Order By: Relevance
“…Winkleman et al used a microfluidic device combined with magnets to continuously separate and collect polystyrene particles of different densities in a flowing stream of aqueous GdCl 3 solution. 16,17 Although the diameters of these polystyrene particles (75 ~ 150 μm) are larger than the crystals used here, our experiments here showed that ~ 80% of particles (volumetric percentage by visual inspection) reached their equilibrium positions within 5 minutes while it takes ~12h for the other ~20% of particles to separate. We therefore believe that it is reasonable to achieve a high degree of separation in a continuous system as long as some considerations are taken into the process design regarding particle size and separation time.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Winkleman et al used a microfluidic device combined with magnets to continuously separate and collect polystyrene particles of different densities in a flowing stream of aqueous GdCl 3 solution. 16,17 Although the diameters of these polystyrene particles (75 ~ 150 μm) are larger than the crystals used here, our experiments here showed that ~ 80% of particles (volumetric percentage by visual inspection) reached their equilibrium positions within 5 minutes while it takes ~12h for the other ~20% of particles to separate. We therefore believe that it is reasonable to achieve a high degree of separation in a continuous system as long as some considerations are taken into the process design regarding particle size and separation time.…”
Section: Discussionmentioning
confidence: 51%
“…The theory of MagLev is described in details elsewhere. 10,11,12 Briefly, under the influence of an external magnetic field, diamagnetic materials of different densities (suspended in a paramagnetic medium) can be levitated to different heights by the balance of magnetic and gravitational forces (Figure 1). Since most materials (especially most organic compounds) are diamagnetic, 2 | J.…”
mentioning
confidence: 99%
“…We have, however, previously demonstrated methods to remove objects separated by MagLev including the use of syringes and tubing with a modified container 49 and the use of a continuous flow system. 50 These methods could be applied to a system that combines MagLev and AMPS, but a low flow rate may be required to maintain a stable interface between phases in a continuous flow method.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Many groups have been working on adapting this principle to particles and cells sorting. For example, Whitesides' group separated synthetic particles according to their densities' difference using paramagnetic salt solutions (Winkleman et al 2007;Mirica et al 2009). Pamme's group demonstrated continuous particle and cell manipulation using paramagnetic salt solution in microfluidic devices (Peyman et al 2009;Rodriguez-Villarreal et al 2011).…”
Section: Introductionmentioning
confidence: 99%